2016
DOI: 10.1186/s13071-016-1875-9
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in the abundance and distribution of Ixodes ricinus and Borrelia burgdorferi (sensu lato) in Scotland: implications for risk prediction

Abstract: BackgroundCases of Lyme borreliosis, a vector-borne zoonosis caused by bacteria in the Borrelia burgdorferi (sensu lato) species group, have increased in recent years in Europe. Knowledge of environmental factors associated with abundance of the tick vector Ixodes ricinus and the pathogen B. burgdorferi (s.l.) is of interest to understand responses to environmental changes, predict variation in risk and to inform management interventions.MethodsNineteen woodland sites across Scotland were surveyed in 2012 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
48
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 70 publications
4
48
4
Order By: Relevance
“…Here we detail the first investigation of LD emergence in treeless habitats in Europe and show that both environmental hazard and human tick bite exposure contribute to higher LD incidence in these settings. In contrast to previous European studies, we found that the hazard amongst treeless habitats can be comparable to forested sites which are traditionally associated with higher LD risk (31,41).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Here we detail the first investigation of LD emergence in treeless habitats in Europe and show that both environmental hazard and human tick bite exposure contribute to higher LD incidence in these settings. In contrast to previous European studies, we found that the hazard amongst treeless habitats can be comparable to forested sites which are traditionally associated with higher LD risk (31,41).…”
Section: Discussioncontrasting
confidence: 99%
“…Within islands with a high incidence of LD, improved grassland, heather moorland, bog and peatland habitats and domestic gardens all had similar tick abundance and prevalence of B. burgdorferi s.l. as mainland forested sites in Scotland (31,41). Our results suggest that the microclimatic conditions in these open habitats, possibly driven by the milder oceanic climate on the Western Isles, can be as conducive to tick survival as in woodlands.…”
Section: Discussionmentioning
confidence: 71%
“…Four genospecies have been recently reported in Scotland, including B. afzelii , B. garinii , B. burgdorferi s.s . and B. valaisiana (Millins et al ., ). Borrelia burgdorferi s.l .…”
Section: Introductionmentioning
confidence: 97%
“…Grey Squirrels are considered to be a significant conservation threat, particularly to the native Red Squirrel (Sciurus vulgaris) (Bertolino et al, 2014). Grey Squirrels carry disease (squirrelpox, Bruemmer et al 2010; Borrelia burgdorferi, the agent of Lyme disease, Millins et al, 2015, Millins et al, 2016, and cause economic losses in forestry (Mayle and Broome, 2013). In the context of this work, evidence suggests that urban Grey Squirrel population size and density is associated with the provision of supplementary food in gardens (Bowers and Breland, 1996;Parker and Nilon, 2008) and there is some evidence that they can competitively exclude birds at supplementary feeders (Hewson et al, 2004;Bonnington et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%